Organizational development as a modern management tool for transformation of the company (case of Ukrainian energy company) - Doroshuk Hanna (Management, 2019)
The article is aimed at formation of the approaches and stages of organizational development for a large vertically integrated company, ensuring the country’s strategic security in the fi eld of energy. The methodological basis of this work is the theory of the company’s life cycle, and it is proposed to complement the mentioned theory with the theory of spiral dynamics, reflecting the evolution of the company’s values.